PERILAKU BERISIKO TINGGI TERTULAR HIV DAN AIDS DI KALANGAN SUPIR TRUK ANTAR KOTA ANTAR PROVINSI - Moch. Zaenal Hakim; Rini Hartini R.A; Lina Favourita; Nono Sutisna (Politeknik Kesejahteraan Sosial Bandung, 2012)
AbstractHIV/AIDS case in Indonesia more increase by the year, in quality nor quantity. Until 2010, identificated 24.131 people living with HIV/AIDS (PLWHA) from many groups includes high risk infected HIV group. As one of high risk man group, truckers is very susceptible infection by HIV/AIDS. The high risk behaviour in truckers and their knowledges about sexual infection disease and HIV/AIDS are still low bring them pass to suspectible and already infected HIV. This conditions are very felt concerned, because if truckers has been infected by HIV, they are big potentially spreading to the other society group by high riskman or not. Truckers are the the main bridge of spreading of HIV/AIDS between prostitutes and society. This qualitative research purpose to know high risk behaviour to infected HIV/AIDS in truckers group in North Coast Area, Subang, West Java. Aspects which is tested including data about characteristic of truck driver, to know the comprehension of truck driver about understanding, transmission, symptom, prevention and care for HIV/AIDS, to know How truck drivers activities in the time rest at northen coast Subang, and providing recommendation for prevention program of HIV/AIDS among truck driver and their environment. Using purposive sampling tehnique, five informants are choosen as primary data resources with two addition informants as secondary data resources for interviewed.The results are showing that the the knowledge about HIV/AIDS of the five informants are low. High risk behaviour to infected HIV in truckers is having sex with women prostitutes by static spouse or changing spouse, did not using condom, having sex with girl friend, having sex in vaginal or oral. The factors that causing high risk sexual behaviour in truckers are pretention, need, and propensity to do something (internal) dan environment factor (external) such as friend influence, and the existing of rest area and prostitution place in the North Coast Strip, Subang, West Java. The Research are recomendating the importance of trucker to change their knowledge, strengthening their comprehension and perception about HIV/AIDS problem by formatting educational group, and strengthening the environment factors that possible to make positive behaviour changing in truckers. Keywords: PLWHA, high risk man, truckers, educational group, positivebehaviour change AbstrakKasus HIV/AIDS di Indonesia semakin meningkat setiap tahun, baik kualitas maupun kuantitas. Sampai dengan tahun 2010 telah ditemui 24.131 Orang Dengan HIV/AIDS (ODHA) dari berbagai kelompok termasuk kelompok berisiko tinggi tertular HIV. Sebagai salah satu kelompok lelaki berisiko tinggi, supir truk sangat rentan tertular HIV/AIDS. Praktek perilaku berisiko tinggi di kalangan supir truk ditambah dengan kurangnya pengetahuan dan pemahaman tentang penyakit menular seksual dan HIV/AIDS, menjadikan mereka rentan dan sudah tertular virus HIV. Keadaan ini sangat mengkhawatirkan, karena ketika supir truk telah tertular virus HIV, mereka berpotensi besar untuk menularkannya kepada kelompok masyarakat lainnya baik yang berisiko tinggi maupun tidak. Supir truk merupakan jembatan utama penularan HIV/AIDS antara wanita pekerja seks dengan masyarakat umum. Penelitian kualitatif ini bertujuan untuk mengetahui perilaku berisiko tinggi tertular HIV/AIDS di kalangan supir truk di kawasan pantai utara Subang Jawa Barat. Aspek yang diteliti adalah karakteristik supir truk; pemahaman supir truk tentang HIV/AIDS dari aspek pengertian, penularan dan gejala-gejala, ujian antibodi, serta pencegahan dan perawatan HIV/AIDS; dan perilaku supir truk dalam memanfaatkan waktu luang dan faktor-faktor yang mempengaruhinya; serta rekomendasi pelayanan yang diperlukan supir truk untuk menangani HIV dan AIDS. Dengan menggunakan tehnik purposive sampling, lima informan telah dipilih sebagai sumber data primer ditambah dengan dua informan tambahan sebagai sumber data sekunder, untuk diwawancara.Hasil penelitian menunjukkan bahwa kelima informan mempunyai pengetahuan dan pemahaman yang sangat kurang tentang HIV/AIDS. Perilaku berisiko tinggi tertular HIV informan adalah berhubungan seks dengan Wanita Tuna Susila (WTS) baik pasangan tetap maupun berganti-ganti, tidak menggunakan kondom, berhubungan seks dengan pacar, melakukan hubungan seks secara vaginal dan oral. Faktor internal perilaku seksual berisiko tinggi, yaitu keinginan, kebutuhan dan hasrat untuk melakukan sesuatu, dan faktor lingkungan (eksternal) adalah pengaruh teman, dan tempat istirahat atau lokasi prostitusi di sepanjang pantai utara Subang Jawa Barat. Penelitian merekomendasikan perlunya memperkuat perubahan pengetahuan, pemahaman dan persepsi para supir truk terhadap masalah HIV/AIDS melalui pembentukan educational group, serta memperkuat faktor lingkungan yang dapat membawa perubahan perilaku secara positif di kalangan supir truk. Katakunci: ODHA, lelaki berisiko tinggi, supir truk, kelompok pendidikan, pengubahan perilaku positif